2021
DOI: 10.1021/acscentsci.0c01237
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Perturbative Molecular Grafting Strategy for Stable and Potent Therapeutic Peptide Ligands

Abstract: The gut-derived incretin hormone, glucagon-like peptide-1 (GLP1), plays an important physiological role in attenuating post-prandial blood glucose excursions in part by amplifying pancreatic insulin secretion. Native GLP1 is rapidly degraded by the serine protease, dipeptidyl peptidase-4 (DPP4); however, enzyme-resistant analogues of this 30-amino-acid peptide provide an effective therapy for type 2 diabetes (T2D) and can curb obesity via complementary functions in the brain. In addition to its medical relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…However, the use of peptides as drugs has long been riddled with problems in regards to low bioavailability, often forcing parenteral administration, as well as related low metabolic stability. Several ways to overcome these issues through chemical modifications of the peptides have been devised, such as PEGylation, N- and C-terminal functionalization, cyclization, and D -amino acid insertion. , N -aroylation- or heteroaroylation of amino acid residues is a strategy that has been used in a number of medicinal chemistry projects aimed at the development of bioactive peptides, where this strategy can improve affinity, reduce metabolic degradation as well as capping of basic amino groups. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…However, the use of peptides as drugs has long been riddled with problems in regards to low bioavailability, often forcing parenteral administration, as well as related low metabolic stability. Several ways to overcome these issues through chemical modifications of the peptides have been devised, such as PEGylation, N- and C-terminal functionalization, cyclization, and D -amino acid insertion. , N -aroylation- or heteroaroylation of amino acid residues is a strategy that has been used in a number of medicinal chemistry projects aimed at the development of bioactive peptides, where this strategy can improve affinity, reduce metabolic degradation as well as capping of basic amino groups. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Fluorination can influence steric properties, the local electrostatics of the peptides and proteins and their hydrophobicity, as well as facilitate interactions with other functional groups through hydrogen or halogen bonding. 8,9 These changes can result in varying overall properties such as the secondary structure propensity, 10 folding behavior 11 and proteolytic stability of peptides [12][13][14] and protein-protein interactions as for instance association kinetics. 15 Studies have shown that the degree of fluorination is crucial for all these properties of peptides and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorination can influence steric properties, the local electrostatics of the peptides and proteins and their hydrophobicity. These changes can result in varying overall properties such as the secondary structure propensity, 8 folding behavior 9 and proteolytic stability of peptides [10][11][12] and protein-protein interactions as for instance association kinetics. 13 Studies have shown that the degree of fluorination is crucial for all these properties of peptides and proteins.…”
Section: Introductionmentioning
confidence: 99%